Relationships Among Toilet Sharing, Water Source Locations, and Handwashing Places Without Observed Soap: A Cross-Sectional Study of the Richest Households in Bangladesh - Mazbahul G Ahamad; Mark Burbach; Fahian Tanin (SAGE Publishing, 2021)
Background: A high percentage of the richest households in Bangladesh lack soap at their handwashing places, a problem that is typically considered to be one of the poor. Objective: We investigated toilet sharing practices, locations of water sources, and relevant sociodemographic factors associated with the observed handwashing places that lack soap in the richest (ninth wealth decile) households in Bangladesh. Methods: We used data from the 2017-18 Bangladesh Demographic and Health Survey (BDHS). Logistic regression technique was used to investigate how toilet sharing practices, water source locations, and different sociodemographic factors were associated with observed handwashing places without soap. Results: We found that 25.8% of the richest households were observed to have no soap at their handwashing places. Of these households, those that shared their toilets with another household were 4.6 times (95% CI 3.15-6.60) more likely to observe handwashing places without soap as compared with those that did not share their toilets. Further, the richest households were 4.2 times (95% CI 2.38-7.33) more likely to observe handwashing places without soap if they collected water from their own yard or plot, and 7.1 times (95% CI 3.61-13.97) more likely to observe handwashing places without soap if they collected water from elsewhere in comparison to the reference group that collected water from their own dwelling. Conclusion: Sharing toilet with other households and location of main water source are associated with handwashing places without observed soap in the richest households in Bangladesh. These results can inform discussions of water availability and soap-handwashing-related policy and program development.